Avascular necrosis following closed reduction for treatment of developmental dysplasia of the hip: A systematic review. (December 2016) - Bradley, Catharine S.; Perry, Daniel C.; Wedge, John H.; Murnaghan, M. L.; Kelley, Simon P.
Background: Avascular necrosis (AVN) is a significant and potentially devastating complication following the treatment of developmental dysplasia of the hip (DDH). The reported rate of AVN following closed reduction for DDH ranges from 4 to 60%, and the resultant influence on hip development remains unclear. Purpose: A systematic review of the literature was undertaken to evaluate the frequency of AVN after more than 5 years of follow-up in children that underwent closed reduction at younger than 2-years of age for DDH. Methods: The search strategy was formulated with key-concepts and keywords identified using the patient problem, intervention, comparison and outcome process. Searches were undertaken using Pubmed, Scopus and Web of Science up to and including May, 2016 to identify potential studies. Results: A total of seven papers met the a priori inclusion and exclusion criteria of this review. The overall rate of significant AVN in 441 patients (538 hips) was 10% at a mean length of follow-up of 7.6 years (5–18.8) following closed reduction. This finding can be used to inform the feasibility of future intervention studies, and act as a baseline for which surgeons to compare their results to a 'standard'.